Job stress and burnout, their impact on nurse performance: a literature study - Epriyanto Epriyanto; Nurul Komari; Ilzar Daud (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
Nursing staff are exposed to high levels of stress and burnout, conditions that can potentially erode professional performance and compromise patient safety. Previous studies have generally been partial and have not been able to comprehensively integrate the latest empirical findings. This article aims to examine the impact of occupational stress and burnout on nurse performance and formulate recommendations for evidence-based intervention strategies. This study used a systematic literature review approach to 25 empirical articles published between 2015 and 2024, sourced from PubMed, ScienceDirect, and Google Scholar databases. The results indicate that occupational stress and burnout have a significant impact on reducing nurse performance, increasing intention to quit, and threatening patient safety. Key triggering factors include excessive workload, long working hours, and limited organizational support. Several interventions have proven effective, including implementing stress management programs, strengthening workplace social support, and restructuring the work environment to make it healthier and more conducive. Occupational stress and burnout are systemic problems that require comprehensive and holistic approaches. Continuous investment in nurses' mental well-being and developing a supportive work environment are key strategies for maintaining optimal performance and improving the quality of healthcare services.